2021
DOI: 10.21037/qims-20-635
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial strain quantification with two- and three-dimensional cardiovascular magnetic resonance based tissue tracking

Abstract: Background: Cardiovascular magnetic resonance based tissue tracking (CMR-TT) was reported to provide detailed insight into left ventricular (LV) contractile function and deformation with both of two-and threedimensional (2/3D) algorithms. This study was designed to investigate the feasibility and reproducibility of these two techniques for measuring LV global and segmental strain, and establish gender-and age-related reference values of global multi-dimensional peak strains among large healthy population.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…Hence, SLE patients with anti-RNP antibody positivity, PAH, and pericardial effusion detected by echocardiography could be considered to further CMR examination. However, these reproducibility results resemble the reported results in several articles (23,41,46); the reproducibility for ventricular peak strain rate obtained by CVI42 software was relatively lower than the peak strain values, particularly for RV in this study. Therefore, there is limited value in the strain rate for the exact quantification and determination of RV function.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, SLE patients with anti-RNP antibody positivity, PAH, and pericardial effusion detected by echocardiography could be considered to further CMR examination. However, these reproducibility results resemble the reported results in several articles (23,41,46); the reproducibility for ventricular peak strain rate obtained by CVI42 software was relatively lower than the peak strain values, particularly for RV in this study. Therefore, there is limited value in the strain rate for the exact quantification and determination of RV function.…”
Section: Discussionsupporting
confidence: 88%
“…It is widely used in the diagnosis of various cardiovascular diseases, including ischemic heart disease. Previous studies have demonstrated an excellent intra-and interobserver reproducibility as well as a good interstudy agreement (11)(12)(13). Our present study also showed similar results.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we applied CMR-TT to quantify LA and RA strains. CMR-TT has been proven reproducible and reliable in assessing LV and RV myocardial deformation ( 12 , 15 ). Recently, its application to atrial strain quantification has been gradually increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to speckle tracking echocardiography (STE), CMR based tissue tracking (CMR-TT) is based on segmentation and tracking of myocardial tissue voxels throughout the cardiac cycle. It has been proven as a promising approach to assess left and right ventricular myocardial strains from routinely available steady-state free precession cine images ( 12 15 ). Due to the thin myocardial wall, insertion of appendage and vena cava, angle dependency and limitation of acoustic windows, the volumetric and mechanical analysis of atrial is challenging using STE ( 16 ).…”
Section: Introductionmentioning
confidence: 99%